Comparative Analysis on South Korea and Indonesia’s Outcome-Based Education (OBE) Resilience Amidst The COVID-19 Pandemic - Mulyaman, Darynaufal; Catherine (Bina Nusantara University, 2022)
The research argued that resilience in human development was maintained by an eminent education system rather than a mere economic performances. It was a comparative analysis of South Korea and Indonesia’s Outcome-Based Education (OBE) resilience amidst the COVID-19 pandemic. The COVID-19 pandemic presented an unprecedented shock to human development. However, some countries handled COVID-19 impacts on their human development progress better than other countries sharing similar economic characteristics. This gap was evident between the G20 and MIKTA middle powers with sizable economic capabilities, South Korea and Indonesia. South Korea remained steady in maintaining its human development index, while Indonesia lagged. Through a qualitative approach, it was used Spady’s Outcome-Based Education theoretical model and gathered secondary data to compare Indonesia and South Korea’s education performances. The findings suggest that maintaining an effective OBE program through addressing physical and nonphysical barriers to education contributes towards resilient human development progress in South Korea, while the opposite is true for Indonesia.